The Relationship between Serum Cystatin-C Levels and Impaired Cognitive Function in Patients with Chronic Kidney Disease - Anggi Anugerah Basir; Yuliarni Syafrita; Syarif Indra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Cystatin-C acts as a neuroprotector in the central nervous system at normal levels, but high serum cystatin-C levels are associated with impaired cognitive function. Serum cystatin-C levels increase in impaired renal function, and cognitive impairment are comorbidities that can increase the morbidity and mortality of chronic kidney disease patients. This study aimed to assess the relationship between serum cystatin-C levels and cognitive function in chronic kidney disease patients. Methods: This study used a cross-sectional design with 73 samples of non-hemodialysis chronic kidney disease patients. Cognitive function was assessed using the MoCa-Ina. Serum cystatin-C levels of all samples were measured by the ELISA method. Data analysis was carried out using SPSS. Results: Impaired cognitive function in CKD patients was found to be 76.7%. The median serum cystatin-C level of CKD patients with impaired cognitive function (n=56) was 1.015 mg/dL, and without cognitive impairment (n=17) was 0.929 mg/dL. There was no significant relationship between serum cystatin-C levels (cut-off point 0.98 mg/dL) and impaired cognitive function (OR : 2.05, 95% CI : 0.680-6.175, p= 0.198). Conclusion: There is no relationship between serum cystatin-C levels and cognitive function impairment in non-hemodialysis chronic kidney disease patients.